The Influence of Product Quality, Service Quality, Customer Satisfaction on Customer Loyalty at Pizza Hut Restaurant - Hanindita, Lisa Putri; Riorini, Sri Vandayuli (inovator, 2023)
This research aims at product quality, service quality, customer satisfaction, and customer loyalty. The sampling technique used was purposive sample, that is people who have eaten at a pizza hut restaurant with a total of 125 respondents used by deploying google form. Hypothesis testing using a partial test (t test), simultaneous test (F test), and the coefficient of determination (R²). The test results prove that product quality, service quality, and customer satisfaction have a positive effect on customer loyalty.